Fluorination-enhanced photoconductive effect in a wide band gap Ca3Ti2O7-xFx thin films. (16th December 2020) - Lu, Hao; Yang, Yang; Luo, Zhongshen; Wu, Sihui; Ji, Yanda; Li, Yang; Zhang, Jinlei; Liu, Guozhen; Jiang, Yucheng; Yang, Hao; Ma, Chunlan; Zhao, Run; et al.
Abstract: In this work, Ca3 Ti2 O7- x F x thin films on (110) SrTiO3 substrates were prepared by two steps as deposited via pulsed laser deposition and fluorinated with polyvinylidene fluoride. Despite the unchanged crystal structure of the fluorinated films, the changed valence state can be used to confirm the incorporation of F −1 and the weakened chemical bond of Ca–O. Furthermore, we found that the photoelectric switch can be observed at a wide range of light wavelength from 405 nm to 808 nm. It is found that the photosensitivity of 4 × 10 4 (405 nm) in the fluorine has been increased by two orders of magnitude, which is most likely due to the deep energy levels in the reduced band gap of 2.3 eV. This work paves the way for the enhanced photoconductive devices via the anionic defect engineering.